The Country Configuration of Global Private Higher Education - Levy, Daniel (International Higher Education, 2019)
A twin reality captures the key country configuration of global private higher education. One reality is the dispersion of the private presence to so many countries in all regions. The other, however, is the heavy, disproportionate concentration of private higher education in the largest country systems.